PENGARUH MEDIA PEMBELAJARAN BERBASIS APLIKASI AUGMENTED REALITY VIRUS TERHADAP METAKOGNITIF MATERI VIRUS PADA SISWA KELAS X SMA NEGERI 16 SAMARINDA - Anis Tri Fransiska (Universitas Muhammadiyah Metro, 2025)
Students in class X SMA Negeri 16 Samarinda have a low understanding of virus material seen in the average value of student tests lower than the KKM value of 75, so it is necessary to use the right learning media to attract interest in learning. this study aims to determine the effect of learning media based on Augmented Reality virus applications on metacognition in class X students. This type of research is using a quantitative approach with quasi-experimental methods and research design Nonequivalent Control Group Design. Sampling using purposive sampling with experimental class X4 and control X5, class determination is done by comparing the average learning outcomes. Data collection techniques and instruments using test questions and questionnaires. The data analysis technique uses Anova with a significance level of 5% with the posttest results having a sig. 0.001, and questionnaire sig. 0.001, which is smaller than 0.05, so Ha is accepted. Based on the results it can be concluded that there is an effect of learning media based on Augmented Reality virus applications on metacognitive virus material in class X students of SMA Negeri 16 Samarinda.